2022
DOI: 10.48550/arxiv.2202.07543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BLUE at Memotion 2.0 2022: You have my Image, my Text and my Transformer

Abstract: Memes are prevalent on the internet and continue to grow and evolve alongside our culture. An automatic understanding of memes propagating on the internet can shed light on the general sentiment and cultural attitudes of people. In this work, we present team BLUE's solution for the second edition of the MEMOTION shared task. We showcase two approaches for meme classification (i.e. sentiment, humour, offensive, sarcasm and motivation levels) using a text-only method using BERT, and a Multi-Modal-Multi-Task tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Giorgi (2021), following an assessment of the literature on memes, proposes to identify memes based on three features: irony, manipulation, and intertextuality. Research on memes also witnessed a rising trend in studies employing computational techniques for the automated recognition and classification of memetic instances (Miliani et al, 2020;Bucur et al, 2022;Theisen et al, 2021). Here, too, memes are identified and sorted depending on the presence of characteristics, like multimodality or recurrent layouts.…”
Section: Meme Research: a Standardized Approachmentioning
confidence: 99%
“…Giorgi (2021), following an assessment of the literature on memes, proposes to identify memes based on three features: irony, manipulation, and intertextuality. Research on memes also witnessed a rising trend in studies employing computational techniques for the automated recognition and classification of memetic instances (Miliani et al, 2020;Bucur et al, 2022;Theisen et al, 2021). Here, too, memes are identified and sorted depending on the presence of characteristics, like multimodality or recurrent layouts.…”
Section: Meme Research: a Standardized Approachmentioning
confidence: 99%
“…We extract features using FasterRCNN (Ren et al, 2015), EfficientNet (Tan and Le, 2019) and VGG (Simonyan and Zisserman, 2015). Bucur et al (2022) showed that EfficientNet features prove useful for sentiment and emotion analyses of meme, while Pramanick et al (2021) prove the efficiency of VGG for detecting harmful memes and identifying their target.…”
Section: Clip and Visualbertmentioning
confidence: 99%